Japanese Marxist: - Bernstein, Gail Lee (Council on East Asian Studies, Harvard University, 1990)
It is the merit of Bernstein's portrait of Kawakami Hajime that he emerges as a recognizable human being, a truly modern figure reflecting in his own life a personal and hard-won balance between traditional Japanese values and the demands of modernization. The heir of a samurai family, an acknowledged authority on economics, a professor at one of Japan's leading universities, an early popularizer of Marxism in Japan, a Japanese Communist on his own unique terms, and, finally, the author of an autobiography that is a classic of modern Japanese literature, Kawakami Hajime is an important figure in the history of modern Japan